2005
DOI: 10.1038/433819a
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic enamel for rapid tooth repair

Abstract: The conventional treatment of dental caries involves mechanical removal of the affected part and filling of the hole with a resin or metal alloy. But this method is not ideal for tiny early lesions because a disproportionate amount of healthy tooth must be removed to make the alloy or resin stick. Here we describe a dental paste of synthetic enamel that rapidly and seamlessly repairs early caries lesions by nanocrystalline growth, with minimal wastage of the natural enamel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
174
0
12

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(194 citation statements)
references
References 8 publications
2
174
0
12
Order By: Relevance
“…25 The reaction solutions were purged with nitrogen gas saturated with water vapor at 37 ± 0.1 °C. The relative supersaturation σ and supersaturation ratio S are given by eq 1: (1) in which υ (=18) is the number of ions in a formula unit of the HAP phase and IAP and K sp are the ionic activity and thermodynamic solubility product (5.52 × 10 −118 mol 18 ) and potassium dihydrogen phosphate (0.020 mol L −1 ) with sodium chloride to maintain the ionic strength I = 0.150 mol L −1 . Amel proteins were added to supersaturated reaction solutions to achieve concentrations ranging from 0.5 to 5.0 μg mL −1 .…”
Section: Hap Crystallization By Constant Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 The reaction solutions were purged with nitrogen gas saturated with water vapor at 37 ± 0.1 °C. The relative supersaturation σ and supersaturation ratio S are given by eq 1: (1) in which υ (=18) is the number of ions in a formula unit of the HAP phase and IAP and K sp are the ionic activity and thermodynamic solubility product (5.52 × 10 −118 mol 18 ) and potassium dihydrogen phosphate (0.020 mol L −1 ) with sodium chloride to maintain the ionic strength I = 0.150 mol L −1 . Amel proteins were added to supersaturated reaction solutions to achieve concentrations ranging from 0.5 to 5.0 μg mL −1 .…”
Section: Hap Crystallization By Constant Compositionmentioning
confidence: 99%
“…10-14 Others have examined applications of external fields 15 and the use of various hydrothermal conditions, including extreme temperature, pressure, and pH. [16][17][18] However, these in vitro studies have not focused on the initial contact between mineral nuclei and organic additives that drive the earliest nucleation events responsible for subsequent directed assembly, yielding the complex morphologies and mineral phases found in enamel.…”
Section: Introductionmentioning
confidence: 99%
“…Recently Yamagishi et al has reported that it is possible to use the fluoridated-apatite to repair early caries lesions directly. 7 We believe that the shape and chemical composition of well defined synthetic fluorapatite nanorods / nanowires have the potential to be layered over carious lesions.…”
Section: Introductionmentioning
confidence: 99%
“…This might occur because HAp initially precipitated at high temperature at the initial pH of 6.0 37) and then the HAp crystal grew epitaxially, or because fibrous OCP nanocrystals were initially formed and then hydrolyzed into HAp crystals 38) during the high temperature treatment at 80°C. The resultant fiber HAp had a lower Ca/P ratio as compared with that of the rodshaped HAp prepared under alkaline conditions, which indicates that calcium ions were exchanged with protons under acidic conditions; hence, HPO 3 2− was observed in the FT-IR spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Various attempts have been undertaken to harden the enamel surfaces or to remineralize tooth enamel by using fluoride 1) , metastable calcium phosphate (CaP) solution 2) , or acidic phosphate fluoride solution 3) treatments. Recently, the direct application of nanoparticulate hydroxyapatite (HAp) -one of the most widely used types of CaP materials 4)-for repairing (remineralizing or hardening) damaged enamel has attracted attention [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%